2004
DOI: 10.1016/j.cellbi.2004.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing effects of bisphenol A on the secretory function of ovine anterior pituitary cells

Abstract: We investigated the action of bisphenol A (BPA) on cellular GH release and content, cell number, GHmRNA expression, and concentrations of cellular cyclic AMP ([cAMP]c) and calcium ion ([Ca2+]c) in primary cultured ovine anterior pituitary cells. The following results were found: (1) BPA as well as nonylphenol (NP) at 10(-6) to 10(-3) M significantly and concentration-dependently suppressed basal and GHRH-stimulated GH release, and the cellular GH content, (2) BPA suppressed the cell number in a time- and conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Although it was not possible to determine the exact nature and location of action in these studies, Katoh et al . (2004) showed that bisphenol exposure affected growth hormone through an effect exerted at the level of the pituitary gonadotrophes, whereas other studies such as those by Wright et al . (2002) with octylphenol, and Lyche et al .…”
Section: Effects On Animal Physiologymentioning
confidence: 95%
“…Although it was not possible to determine the exact nature and location of action in these studies, Katoh et al . (2004) showed that bisphenol exposure affected growth hormone through an effect exerted at the level of the pituitary gonadotrophes, whereas other studies such as those by Wright et al . (2002) with octylphenol, and Lyche et al .…”
Section: Effects On Animal Physiologymentioning
confidence: 95%
“…* P \ 0.05, ** P \ 0.01, as compared with the respective sbGH treatment alone using one-way ANOVA information on the action of BPA on the somatotropic axis. The only study was in ovine pituitary cells showing that BPA could significantly suppress basal and growth hormone releasing hormone (GHRH)-stimulated GH release as well as the cellular GH content (Katoh et al 2004). In the present study, using fish primary hepatocytes and a fish liver cell line, the actions of BPA on the somatotropic axis were delineated at the gene expression and signal transduction levels.…”
Section: Discussionmentioning
confidence: 98%
“…Some reports have shown that BPA, besides disrupting the growth of the comb and testes in male chicken (Furuya et al 2003), could also affect the rat brain somatostatin receptor subtype, which is an important component of the somatotropic axis (Facciolo et al 2002). Further studies on the pituitary, the master gland of the somatotropic axis regulating postnatal growth, demonstrated that BPA possessed suppressive actions on growth hormone (GH) synthesis and release, probably via impairment of the cellular signal transduction systems (Katoh et al 2004). GH exerts its action by binding to the growth hormone receptor (GHR) and activating the post-receptor signaling events.…”
mentioning
confidence: 96%
“…Neuroendocrine data in rodents and sheep suggest effects on female hypothalamicpituary-gonadal (HPG) axis organization (≥50 µg/kg b.w. per day, non-oral route) and function (≥5 mg/kg b.w./day, non-oral route), that is at doses higher than the Point of Departure used for TDI derivation (Katoh et al, 2004). The specific mechanisms by which this occurs remain to be identified, but some data suggest that the pattern of luteinizing hormone release may be altered by exposure, resulting in blunted secretion and resistance to feedback.…”
Section: Neurotoxicity and Behavioural Toxicitymentioning
confidence: 99%